How to Turn Different Gardening Techniques into Workouts as a Healthy Activity - Haijian Pang; Huanhuan Tian, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The objective of this study is to explore how classical gardening techniques can be adapted into effective physical workouts, particularly in constrained spaces, promoting health and wellness through active participation in gardening. By using the example of "Jiangjun pear" packaging design from Dawu County—an old revolutionary base area—this research extends to how landscape gardening not only serves aesthetic and cultural purposes but can also be transformed into a series of physical activities that benefit health. This involves examining key elements of landscape geometry to design gardening activities that serve dual purposes: enhancing cultural heritage and providing a moderate to vigorous physical workout. This study introduces a methodology that encompasses penetration, transformation, integration, innovation, and evaluation to embed these gardening techniques into a workout regimen. The focus is on converting the motions and efforts involved in traditional gardening, such as digging, planting, and pruning, into structured physical exercises that improve fitness levels and can be performed in small or restricted areas. The conversion of these gardening actions into systematic workouts aims to offer a beneficial reference for both the agricultural and health industries, enhancing the user experience by promoting both cultural appreciation and physical health. Furthermore, this research demonstrates the practical applicability of these adapted gardening techniques through a lively, culturally rich three-dimensional model of garden-based workouts. The design logic and theoretical framework developed here aim to foster a deeper understanding of how everyday activities like gardening can be innovatively rethought as comprehensive, health-promoting exercises. This approach not only broadens the innovative path of integrating cultural and physical activities but also supports the revitalization of rural areas by promoting both the physical health of individuals and the cultural heritage associated with agricultural practices. The final outcome seeks to enhance the market brand competitiveness of agricultural products while significantly contributing to the field of health and wellness.